2000
DOI: 10.1104/pp.124.2.767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated [CO2] and Nitrogen Nutrition on Cytokinins in the Xylem Sap and Leaves of Cotton

Abstract: We measured the level of xylem-derived cytokinins (CKs) entering a cotton leaf, and the CK levels in the same leaf, thus enabling xylem sap and foliar CKs to be compared concurrently. Although zeatin was the dominant CK in xylem sap, zeatin, dihydrozeatin, and N 6 -(2-isopentenyl) adenine were present in approximately equimolar levels in leaves. Elevated [CO 2 ] (EC) has an effect on the levels of cytokinins in sap and leaf tissues. This effect was modulated by the two levels of root nitrogen nutrition (2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 55 publications
2
80
0
4
Order By: Relevance
“…For the analysis, we used a simplified method for quantifying cytokinins in potentially active forms. Cytokinin ribosides and nucleotides were converted to bases during the process of anhydrous methanolysis, whereas the O-, 7-, and 9-glucoside linkages were not cleaved appreciably Yong et al 2000). Thus, Z, DZ, iP, OGZ, and OGDZ levels presented in this paper refer to the total content of each compound (base) in free, riboside and nucleotide forms.…”
Section: Elevated Levels Of Cytokinins In Sps Mutantsmentioning
confidence: 88%
See 1 more Smart Citation
“…For the analysis, we used a simplified method for quantifying cytokinins in potentially active forms. Cytokinin ribosides and nucleotides were converted to bases during the process of anhydrous methanolysis, whereas the O-, 7-, and 9-glucoside linkages were not cleaved appreciably Yong et al 2000). Thus, Z, DZ, iP, OGZ, and OGDZ levels presented in this paper refer to the total content of each compound (base) in free, riboside and nucleotide forms.…”
Section: Elevated Levels Of Cytokinins In Sps Mutantsmentioning
confidence: 88%
“…This procedure (Chaudhury et al 1993;Wang et al 1995) converts 9-ribosides and nucleotides to bases, whereas O-, 7-, and 9-glucoside linkages are not cleaved appreciably. After three-step column purification (Chaudhury et al 1993), the bases (free plus bound and glucosides) were further purified by HPLC for quantification by scintillation proximity immunoassay Yong et al 2000). Cytokinin bases (Z, DZ, and iP) and Z-9-glucoside were measured directly, but the O-glucosides were first hydrolyzed to bases with ␤-glucosidase (Yong et al 2000).…”
Section: Quantification Of Cytokininsmentioning
confidence: 99%
“…Fangmeier et al, 2002;Thomas et al, 2006), what we found in this study ( Table 2) is in consistence with Wang et al (2015) where leaf K was not clearly different at eO 3 and eCO 2 from that grown under ambient. It was possibly because the decreased photosynthetic rate (Kitao et al, 2015) was somehow offset by the enhanced phytohormones induced by eO 3 or eCO 2 (Yong et al, 2000;Winwood et al, 2007;Matyssek et al, 2012), thereby regulating the foliar K independent with the specific gas treatments. Moreover, the high leaf K in August, both the 1 st and 2 nd flush, was likely connected with remobilisable stored water or with succulence so that K may be accumulated in vacuoles (Von Willert et al, 1992;Cornelissen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For sap collection with minimal perturbation, xylem water of an intact leaf was sampled concurrently from primary and secondary veins using a root pressure chamber (Yong et al, 2000). While the whole root system of the plant was enclosed and pressurized in the chamber, a light incision was made on the leaf vein with a sharp razor blade.…”
Section: Vein Xylem Water Samplingmentioning
confidence: 99%